Kymographic Recording of Clot Retraction: Effects of Papaverine. Theophylline and Cytochalasin B - Majno, G; Bouvier, C.A; Gabbiani, G; Ryan, G.B; Statkov, P (Thrombosis and Haemostasis, 1972)
Clot retraction was studied by setting up ribbon-shaped clots in a pharmacological bath and recording the progress of contraction on a kymograph. Drugs could be added to the bath or washed out at any stage. Papaverine, theophylline and cytochalasin B each reversed the upward course of the kymograph tracing ; contraction began again when the drugs were washed from the bath. This phenomenon resembles the behaviour of smooth muscle under similar circumstances.